The toxic dinoflagellate Alexandrium minutum affects oyster gamete health and fertilization potential. (July 2021) - Castrec, Justine; Fabioux, Caroline; Le Goïc, Nelly; Boulais, Myrina; Soudant, Philippe; Hégaret, Hélène
Abstract: Dinoflagellates from the globally distributed genus Alexandrium are known to produce both paralytic shellfish toxins (PST) and uncharacterized bioactive extracellular compounds (BEC) with allelopathic, ichthyotoxic, hemolytic and cytotoxic activities. In France, blooms of Alexandrium minutum appear generally during the spawning period of most bivalves. These blooms could therefore alter gametes and/or larval development of bivalves, causing severe issues for ecologically and economically important species, such as the Pacific oyster Crassostrea (= Magallana ) gigas . The aim of this work was to test the effects of three strains of A. minutum producing either only PST, only BEC, or both PST and BEC upon oyster gametes, and potential consequences on fertilization success. Oocytes and spermatozoa were exposed in vitro for 2 h to a range of environmentally realistic A. minutum concentrations (10–2.5 × 10 4  cells mL −1 ). Following exposure, gamete viability and reactive oxygen species (ROS) production were assessed by flow cytometry, spermatozoa motility and fertilization capacities of both spermatozoa and oocytes were analysed by microscopy. Viability and fertilization capacity of spermatozoa and oocytes were drastically reduced following exposure to 2.5 × 10 4  cells mL −1 of A. minutum . The BEC-producing strain was the most potent strain decreasing spermatozoa motility, increasing ROS production of oocytes, and decreasing fertilization, from the concentration of 2.5 × 10 3  cells mL −1 . This study highlights the significant cellular toxicity of the BEC produced by A. minutum on oyster gametes. Physical contact between gametes and motile thecate A. minutum cells may also contribute to alter oyster gamete integrity. These results suggest that oyster gametes exposure to A. minutum blooms could affect oyster fertility and reproduction success. Highlights: Oyster spermatozoa and oocytes were exposed in vitro to Alexandrium minutum strains. Viability and fertilization capacity of gametes were drastically reduced. The toxicity of Alexandrium minutum upon oyster gametes is strain-specific. A non-PST-producing strain increased reactive oxygen species production in oocytes. This strain also decreased spermatozoa motility and gamete fertilization.